Effect of heavy metal compounds on the plants development as biologically active substances (Eurasian Journal of Ecology, 2018)
The effect of color industrial enterprise pollutant on envirement at workhas carry out. Aims of work – to investigate by cytogenetically methods ofheavy metalls compounds of mutagenic activity on plants and their influence fenologically phasis developet of plants. Has obtained of fenologically phasis developet of plants, which is growing near of industrial zone.Hower, of natural population of Hordeum leporinum plant species has increase of heavy metalls mutagenic activity. The Hordeum leporinum plantspecies has obtained of frecuency of genomic mutation from Shymkententerprise zone. The comparatve analayzing of freguency of aneuploydcells depend of heavy metalls content in Hordeum leporinum plant speciesis showed the high level of correlation coefficient (г=0,94). Has obtinedat cells Hordeum leporinum plant species from Shymkent enterprise zone,which was intensive polluted of is obtined the freguence of aneuploydcells more then controlle group. High consentration of heavy metalls inplant body have resistence and transmitted by cyclinke of food safety ofanimals and human health. At reaserch results is showed the cromosomenumber of Hordeum leporinum plant species changed as mutagenic effectof heavy metalls, which will be genetically risks.Key words: heavy metals, karyotype, mutagenic factors, hyperdiploidcells, hypodiploid cells.